A LIVING COMMUNITY PRESENCE: TRAINING OF END OF LIFE CARE VOLUNTEERS. Issue 1 (1st March 2014) - Doyle, R; Nolan, K; Gambles, M; Roberts, A; Smeding, R; Mason, S; Ellershaw, JE
Abstract : Introduction: In British healthcare the majority of people die in hospitals. Volunteering in this setting focuses on fundraising and practical tasks but excludes bedside care. OPCARE 9, an EU-FP7 funded project, highlighted how many European countries have utilized volunteers in caring for dying patients, providing support for patients and families, whilst re-introducing a valuable sense of 'community'. Aim(s) and method(s): This project sought to distil existing international expertise and experience to develop and evaluate a Care of the Dying Volunteer Programme to support patients in the last hours or days of life in a hospital setting (North West of England). A bespoke training program, reflecting those delivered in the Netherlands, Germany and Italy, was developed for the UK, to enhance volunteer's existing skills and personal qualities by drawing on their life experiences. A mixed methods approach was engaged where, in addition to volunteers' longitudinal reflective assessments of the training and experience of providing support, clinical staff and patients' relatives provided qualitative and quantitative feedback where volunteers were engaged. Results: 19 volunteers completed the training programme and provided support to 14 patients in 6 wards. Data demonstrates that volunteers' confidence improved, that they found the training interesting, enjoyable and the content fit for purpose. Clinical staff welcomed volunteers on the whole, as did relatives, identifying the volunteers as filling an important "gap" in support. Conclusion(s): The training program proved effective in preparing volunteers. It has now been further developed in response to the findings of this research, and could be replicated in other clinical sites.